2023
DOI: 10.1093/mnras/stad2446
|View full text |Cite
|
Sign up to set email alerts
|

The white dwarf mass–orbital period relation under wind mass-loss

Shi-Jie Gao,
Xiang-Dong Li

Abstract: Helium white dwarfs (HeWDs) are thought to form from low-mass red giant stars experiencing binary interaction. Because the helium core mass of a red giant star is closely related to the stellar radius, there exists well-known relation between the orbital period (Porb) and the mass (MWD) of the HeWDs, which is almost independent of the type of the companion star. Traditional derivation of the MWD–Porb relation generally neglected the effect of wind mass loss from the red giants, while observations show that win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 139 publications
0
5
0
Order By: Relevance
“…Figure 9 shows the orbital period as a function of the core mass for the NS-He WD systems with well-established masses (Gao & Li 2023). A relation between period and WD mass can be established by modeling systems (Lin et al 2011), and this is also shown.…”
Section: Neutron Star-white Dwarf Binaries and Recycled Pulsarsmentioning
confidence: 92%
See 1 more Smart Citation
“…Figure 9 shows the orbital period as a function of the core mass for the NS-He WD systems with well-established masses (Gao & Li 2023). A relation between period and WD mass can be established by modeling systems (Lin et al 2011), and this is also shown.…”
Section: Neutron Star-white Dwarf Binaries and Recycled Pulsarsmentioning
confidence: 92%
“…Table 5 contains no fully recycled pulsars, i.e., pulsars with spin periods less than 10 ms. Four systems contain a mildly (or close to mildly) recycled pulsar with spin periods  35 ms. Three systems, J0823+0159, J1803−2712, and J1822−0848, have spin periods > 300 ms. Long orbital period systems like IGR J16194−2810 are clearly not MSP progenitors. The absence in Table 5 of NS-He WD pulsars with orbital periods longer than 1000 days suggests that IGR J16194−2810 is at the long end of LMXB orbital periods 2 of Gao & Li 2023). Where the uncertainties in the mass are large enough to be plotted they are shown as a horizontal line.…”
Section: Neutron Star-white Dwarf Binaries and Recycled Pulsarsmentioning
confidence: 99%
“…However, for an individual binary, TS99 pointed out that P orb and M WD increase with increasing fractions of mass and angular momentum loss. Gao & Li (2023) studied the P orb -M WD relation under wind mass loss and pointed out that tidally enhanced wind can play an important role for helium WD binaries in wide orbits. In addition, the P orb -M WD relation is ascertained from a circular orbit.…”
Section: Period-wd Mass Relationmentioning
confidence: 99%
“…The final stage of the close binary evolution through Roche lobe overflow results in a relationship between the primary masses and the orbital periods. These values are shown in Figure 8, where we compare our target with ELM WD-WD binaries from an ELM survey (Brown et al 2020) and ELM WD-NS binaries from Gao & Li (2023). The short-period binaries (P < 8 hr) with a broad distribution of primary masses are from the common envelope channel, whereas the Roche lobe channel forms a relatively narrow locus of objects with a strong mass-period dependence.…”
Section: Comparison With Theoretical Modelsmentioning
confidence: 99%
“…Masses vs. orbital periods for ELM WDs binaries are plotted along with both solutions obtained for our target. Binaries with WD companions are selected fromBrown et al (2020), while binaries with NS companions are selected fromGao & Li (2023). The dashed line is the theoretical mass-orbital period relation for the Roche lobe channel fromGao & Li (2023).…”
mentioning
confidence: 99%